Plan Estratégico de crecimiento Sushi White Label Restaurants (2023)
Sushi White Label Restaurants is an Asian food restaurant chain aiming to increase its market share. To achieve this, the company must choose between two growth strategies evaluated in three scenarios and measured through four performance indicators. This document analyzes the performance of each strategy, which has as fundamental pillars the investments that must be made in maintenance, service personnel, marketing, capital requested from the parent company, food price and menu expenses. The objective is to achieve, over ten years, the opening of at least two hundred restaurants, have performance indicators greater than 95%, have a return on investment greater than 30% and maximize its profits.